Sexual dysfunction in infertile women - Zahra Zare; Malihe Amirian; Nahid Golmakani; Reza Mazlom; Laal Ahangar (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Sexual problems have different effects on the life of people by influencing their interpersonal and marital relationships and satisfaction. Relationship between sexual dysfunctions and infertility can be mutual. Sexual dysfunction may cause difficulty conceiving but also attempts to conceive, may cause sexual dysfunction. Objective: This paper compares sexual dysfunction in fertile and infertile women. Materials and Methods: In this cross-sectional study, 110 infertile couples referring to Montasarieh Infertility Clinic and 110 fertile couples referring to five healthcare centers in Mashhad were selected by class cluster sampling method. Data collection tools included demographic questionnaire and Glombok-Rust Inventory of Sexual Satisfaction. Data were analyzed through descriptive and analytical statistical methods by SPSS. Results: There was no significant difference in total score of sexual problems and other dimensions of sexual problems (except infrequency) in fertile 28.9 (15.5) and infertile 29.0 (15.4) women. Fertile women had more infrequency than infertile women (p=0.002). Conclusion: There was no significant difference between fertile and infertile women in terms of sexual problems. Paying attention to sexual aspects of infertility and presence of programs for training of sexual skills seems